2010
DOI: 10.1637/9070-091409-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Ornithobacterium rhinotracheale North American Field Isolates Express a Hemolysin-Like Protein

Abstract: Ornithobacterium rhinotracheale is a gram-negative bacterium responsible for the sporadic outbreaks of airsacculitis in poultry, accounting for millions of dollars in losses to the poultry industry annually. Although the organism was originally classified as non-beta-hemolytic, recent North American field isolates of O. rhinotracheale obtained from pneumonic lungs and air sacs indicated hemolytic activity on blood agar plates upon extended incubation for 48 hr at room temperature in air after initial incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…The pathogen was relatively recently discovered and is distributed worldwide in chickens and turkeys, as well as in other avian species (15)(16)(17). O. rhinotracheale is associated with respiratory diseases and causes significant economic loss to the poultry industry (17)(18)(19).…”
mentioning
confidence: 99%
“…The pathogen was relatively recently discovered and is distributed worldwide in chickens and turkeys, as well as in other avian species (15)(16)(17). O. rhinotracheale is associated with respiratory diseases and causes significant economic loss to the poultry industry (17)(18)(19).…”
mentioning
confidence: 99%
“…However, the presence of extensive and unusual β-hemolytic activity has been recently reported among North American and Argentinean field isolates after the 48-h-period following incubation at room temperature (Walters et al, 2009;Tabatabai et al, 2010;Gornatti Churria et al, 2011). Tabatabai et al (2010) characterized and demonstrated the β-hemolytic activity of O. rhinotracheale isolates using in vitro kinetic hemolysis assays with sheep red blood cells, western blotting with leukotoxin-specific monoclonal antibodies, and isobaric tagging and quantitative analysis of O. rhinotracheale outer membrane protein digest preparation. Moreover, Walters et al (2011) have recently developed an embryo lethality assay to determine potential virulence differences between hemolytic and non-hemolytic O. rhinotracheale strains isolated from turkeys in Virginia´s Shenandoah Valley, USA.…”
Section: Etiologymentioning
confidence: 99%
“…van Empel and Hafez (1999) and Chin and Charlton (2008) also proposed the use of blood agar plates without antibiotic to prevent missing 10% of the antibiotic-susceptible isolates. Ornithobacterium rhinotracheale was first identified as a non-hemolytic microorganism (van Empel and Hafez, 1999;Hafez, 2002;Canal et al, 2005;Chin and Charlton, 2008;, such as the ATCC 51463 strain of O. rhinotracheale (Tabatabai et al, 2010;Gornatti Churria et al, 2011). However, the presence of extensive and unusual β-hemolytic activity has been recently reported among North American and Argentinean field isolates after the 48-h-period following incubation at room temperature (Walters et al, 2009;Tabatabai et al, 2010;Gornatti Churria et al, 2011).…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations